2021
DOI: 10.1667/rade-20-00265.1
|View full text |Cite
|
Sign up to set email alerts
|

The Threshold Effects of Low-Dose-Rate Radiation on miRNA-Mediated Neurodevelopment of Zebrafish

Abstract: The biological effects and regulatory mechanisms of low-dose and low-dose-rate radiation are still rather controversial. Therefore, in this study we investigated the effects of low-dose-rate radiation on zebrafish neurodevelopment and the role of miRNAs in radiation-induced neurodevelopment. Zebrafish embryos received prolonged gamma-ray irradiation (0 mGy/h, 0.1 mGy/h, 0.2 mGy/h, 0.4 mGy/h) during development. Neurodevelopmental indicators included mortality, malformation rate, swimming speed, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…From a genetic perspective, miRNAs were involved in cell proliferation, differentiation, and apoptosis and affect the development and maturation of the brain and extensively regulate neuroendocrine processes. 43 , 44 At the same time, personality disorder and schizophrenia are closely related to brain development and neuroendocrine. 45 , 46 The results indicated that miRNA may be involved in the pathophysiological process of both personality disorder and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…From a genetic perspective, miRNAs were involved in cell proliferation, differentiation, and apoptosis and affect the development and maturation of the brain and extensively regulate neuroendocrine processes. 43 , 44 At the same time, personality disorder and schizophrenia are closely related to brain development and neuroendocrine. 45 , 46 The results indicated that miRNA may be involved in the pathophysiological process of both personality disorder and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%